Odpowiedź:
zad 1
3(2x - 5) = 1 - 4x
6x - 15 = 1 - 4x
6x + 4x = 1 + 15
10x = 16
x = 16/10 = 1 6/10 = 1 3/5 ≠ 1,5
liczba 1,5 nie spełnia równania
zad 2
a)
5x + 2 = 7 - 3x
5x + 3x = 7 - 2
8x = 5
x = 5/8
b)
- 6(x + 1) = 24
- 6x - 6 = 24
- 6x = 24 + 6 = 30
6x = - 30
x = - 30/6 = - 5
c)
- 7(x - 2) = 3x - 1
- 7x + 14 = 3x - 1
- 7x - 3x = - 1 - 14
- 10x = - 15
10x = 15
x = 15/10 = 1 5/10 = 1,5
d)
- 0,5(- x - 6) = - x
0,5x + 3 = x
0,5x - x = - 3
- 0,5x = - 3
0,5x = 3
x = 3 : 0,5 = 6
e)
x/5 - 3 = x + 1/5 | * 5
x - 15 = 5x + 1
x - 5x = 1 + 15
- 4x = 16
4x = - 16
x = - 16/4 = - 4